Ibogaine Acute Administration in Rats Promotes Wakefulness, Long-Lasting REM Sleep Suppression, and a Distinctive Motor Profile - González, Joaquín; Prieto, José P.; Rodríguez, Paola; Cavelli, Matías; Benedetto, Luciana; Mondino, Alejandra; Pazos, Mariana; Seoane, Gustavo; Carrera, Ignacio; Scorza, Cecilia; Torterolo, Pablo (Frontiers in Pharmacology, 2018)
Ibogaine is a potent psychedelic alkaloid that has been the focus of intense research because of its intriguing anti-addictive properties. According to anecdotic reports, ibogaine has been originally classified as an oneirogenic psychedelic; i.e., induces a dream-like cognitive activity while awake. However, the effects of ibogaine administration on wakefulness (W) and sleep have not been thoroughly assessed. The main aim of our study was to characterize the acute effects of ibogaine administration on wakefulness and sleep. For this purpose, polysomnographic recordings on chronically-prepared rats were performed in the light phase during 6 hours. Animals were treated with ibogaine (20 and 40 mg/kg) or vehicle, immediately before the beginning of the recordings. Furthermore, in order to evaluate associated motor behaviors during the W period, a different group of animals was tested for two hours after ibogaine treatment on an open field with video-tracking software. Compared to control, animals treated with ibogaine showed an increase in time spent in W. This effect was accompanied by a decrease in slow wave sleep (SWS) and rapid-eye movements (REM) sleep time. REM sleep latency was significantly increased in animals treated with the higher ibogaine dose. While the effects on W and SWS were observed during the first 2 hours of recordings, the decrement in REM sleep time was observed throughout the recording time. Accordingly, ibogaine treatment with the lower dose promoted an increase on locomotion, while tremor and flat body posture were observed only with the higher dose in a time-dependent manner. In contrast, head shake response, a behavior which has been associated in rats with the 5HT2A receptor activation by hallucinogens, was not modified. We conclude that ibogaine promotes a waking state that is accompanied by a robust and long-lasting REM sleep suppression. In addition, it produces a dose-dependent unusual motor profile along with other serotonin-related behaviors. Since ibogaine is metabolized to produce noribogaine, further experiments are needed to elucidate if the metabolite and/or the parent drug produced these effects.